Mathematical Reasoning of High School Students in Solving AKM Geometry and Measurements Problem Viewed from Multiple Intelligences - Putri, Sabrina Wimala; Ekawati, Rooselyna (Universitas Negeri Surabaya, 2024)
Mathematical reasoning is needed in solving AKM problems. Mathematical reasoning can be shown through geometry material. One of the factors that influence mathematical reasoning is multiple intelligences. Multiple intelligence is a theory presented by Gardner which states that each individual has eight intelligences. The three intelligences that affect the learning process of mathematics are logical-mathematical, linguistic, and visual-spatial intelligence. This study aims to describe students' mathematical reasoning in solving AKM problems about geometry and measurement content viewed from multiple intelligences. This research is qualitative research. The subjects of this study were three senior high school students consisting of one person each who has dominant logical-mathematical, linguistic, and visual-spatial intelligence. Data collection was carried out by providing multiple intelligence questionnaires, AKM geometry and measurements problems, and interviews. The data were analyzed based on the selected mathematical reasoning indicators. The results of the study show that: Student with dominant logical-mathematical intelligence analyzing a problem by giving reasons based on important information using logic. Students with dominant linguistic intelligence and students with dominant visual-spatial intelligence analyzing a problem by giving reasons using the help of an image that represents the shape described in the problems. Each student implementing a strategy to solve the problem according to what was planned in the previous stage by giving reasons based on the results to be obtained. In reflecting on a solution to a problem, each student draws a conclusion by giving reasons based on the results obtained from implementing the strategy and providing evidence by giving reasons based on the calculation results.